Trends in pediatric firearm-related injuries and disparities in acute outcomes - Mulugeta, Makda G.; Bailey, Gabrielle; Parsons, Kendall; Gillespie, Scott; Johnson, Laura M.; Doh, Kiesha Fraser; Reisner, Andrew; Blackwell, Laura S. (Frontiers in Public Health, 2024)
Background Firearm-related injuries (FRI) are an increasing cause of death and injury in children. The etiology for this rise is multifactorial and includes socioeconomic factors. Despite its prevalence and documented increase over COVID-19, there is a paucity of research on disparities and the influence of social determinants of health (SDH) in pediatric FRI. This study aims to explore the epidemiology of this vulnerable population in Atlanta, trends over time and relevant dates such as COVID-19 and a state firearm law, and disparities in clinical outcomes. Methods Retrospective cohort of patients with FRI (0–20 years-old, x̄=9.8, Median = 11) presenting to our hospital EDs from January 2014 to April 2023 (N = 701) and eligible for the Trauma Registry. This period includes two major events, namely the COVID-19 pandemic (March 2020), and passage of state law Constitutional Carry Act (SB 319) (April 2022), allowing for permit-less concealed firearm carry. Single series interrupted time series (ITS) models were run and clinical outcome differences between race and insurance groups were calculated unadjusted and adjusted for confounders using inverse propensity treatment weights (IPTW). The primary outcome was mortality; secondary are admission and discharge. Results Majority of FRI involved patients who were male (76.7%), Black (74.9%), publicly insured (82.6%), ≤12 years-old (61.8%), and injured by unintentional shootings (45.6%) or assault (43.7%). During COVID-19, there was a sustained increase in FRI rate by 0.42 patients per 1,000 trauma visits per month (95% CI 0.02–0.82, p = 0.042); post-SB 319 it was 2.3 patients per 1,000 trauma visits per month (95% CI 0.23–4.31, p = 0.029). Publicly insured patients had 58% lower odds of mortality than privately insured patients (OR 0.42, 95% CI 0.18–0.99, p = 0.047). When controlled for race and mechanism of injury, among other confounding factors, this association was not significant (p = 0.652). Conclusion Pediatric FRI are increasing over time, with disproportionate burdens on Black patients, at our hospitals. Disparities in mortality based on insurance necessitate further study. As social and economic repercussions of COVID-19 are still present, and state firearm law SB 319 is still in effect, assessment of ongoing trends is warranted to inform preventative strategies.